Association of missense substitution of A49T and V89L in the SRD5A2 gene with prostate cancer in Turkish patients - TİNAY, İLKER (WALTER DE GRUYTER GMBH, 2017)
Objective: To determine the association of missense substitution of alanine 49 threonine (A49T) and valine 89 leucine (V89L) in the steroid-5-alpha-reductase type II (SRD5A2) gene with prostate cancer in Turkish patients. Methods: Eighty patients with prostate cancer and 76 healthy control subjects were evaluated for A49T and V89L polymorphisms in the SRD5A2 gene mutations via real time fluorescence PCR and melting curve analysis. Results: Patients and controls were similar in terms of allele frequencies for polymorphic markers A49T and V89L in the SRD5A2 gene. Most patients had T2b (51.3%), N0 (96.3%) stage tumors with Gleason Score of >= 6 (82.7%) and surgical margin in 28.8%. While 81.3% had no seminal vesicle invasion, 36.3% had capsular invasion. Carrying the 49T allele was associated with higher likelihood of positive surgical margin status (27.5% in 49A vs. 75.0% in 49T, p = 0.038) and Gleason Scores of >= 7 (47.5% in 49A vs. 100.0% in 49T, p = 0.032) than 49A allele. Conclusion: Our findings revealed no significant difference between patient and control groups in terms of allele frequencies of polymorphic markers in the SRD5A2 gene. T allele was only shown in the patient group. Carrying the 49T allele was associated with higher tumor aggressiveness in A49T polymorphism.
Keywords: 5 alpha-Reductase gene; Polymorphism; Prostate cancer; SRD5A2 gene; Missense substitution; 5-ALPHA-REDUCTASE TYPE-II; PATHOLOGICAL CHARACTERISTICS; ANDROGEN PATHWAY; RISK; POLYMORPHISMS; INHIBITORS; MEN; AGGRESSIVENESS; EPIDEMIOLOGY; METAANALYSIS